PSYCHOLOGICAL IMPACTS OF NURSING PROFESSIONALS AGAINST THE COVID-19 PANDEMIC: AN INTEGRATIVE REVIEW - Guispe Pinheiro de Almeida, Angellywoodiany; Eduarda Almeida de Souza, Cicera; Silva Oliveira, Geane; Charllub Pereira Bezerra, Yuri; do Nascimento Andrade Feitosa, Ankilma (Health and Society, 2022)
Introduction: We know the importance of the nurse professional in their work in the care of patients with covid 19, but we must recognize that their work also puts them at risk and this generates concerns that can worsen, leading them to develop psychological disorders. So this study justifies itself in showing the difficulties faced by health professionals, emphasizing the professional nurse, throughout the time that they worked, in assistance, during the covid 19 pandemic and aims to show us which alternatives these professionals have to have their mental health back; free from psychological burdens. Objective: To analyze the psychological impacts suffered by the nursing team, as well as to present the main strategies to improve the mental health of these professionals. Methodology: This is an integrative literature review, carried out through a bibliographic survey in the LILACS, SCIELO and VHL databases. Results and Discussions: The literature showed that most health professionals suffered psychological impacts such as depression, anxiety, mood disorders and phobias. Such consequences are directly related to fear, illness from the virus, family losses and the grieving process. This emotional suffering in the face of any contamination picture is marked as the main aggravating factor of mental health. Conclusion: This study was carried out in order to identify the psychological problems that most affect nursing professionals on the front line in the fight against the pandemic. The objective defined for this study was achieved, allowing to demonstrate the main predisposing factors for such circumstances, as well as the intervention strategies to be carried out.